2016
DOI: 10.1249/mss.0000000000000808
|View full text |Cite
|
Sign up to set email alerts
|

Similar Hemoglobin Mass Response in Hypobaric and Normobaric Hypoxia in Athletes

Abstract: HH and NH evoked similar Hb(mass) increases for the same hypoxic dose and after 18-d LHTL. The wide variability in individual Hb(mass) responses in HH and NH emphasizes the importance of individual Hb(mass) evaluation of altitude training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 39 publications
8
63
3
1
Order By: Relevance
“…This statement is supported by evidence demonstrating the effectiveness of natural‐altitude LHTL on endurance performance in well‐trained runners . The results from this highly cited study tended to be confirmed by subsequent controlled research using natural‐altitude LHTL in well‐trained triathletes . Furthermore, a controlled study has verified this hypothesis in elite swimmers .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…This statement is supported by evidence demonstrating the effectiveness of natural‐altitude LHTL on endurance performance in well‐trained runners . The results from this highly cited study tended to be confirmed by subsequent controlled research using natural‐altitude LHTL in well‐trained triathletes . Furthermore, a controlled study has verified this hypothesis in elite swimmers .…”
Section: Introductionsupporting
confidence: 61%
“…According to a power analysis of previous results from our group showing an increase in Hb mass of 42.3 ± 21.7 g at altitude (mean ± SD of differences), a sample size of 6 subjects provides a 95% power to detect a 5% change in Hb mass with a two‐sided α of 5 %. This dataset was selected because (a) power analysis should be based on data obtained by the same assessment methodology, and in this study, we used the same CO‐rebreathing assessment methodology; and (b) the reported Hb mass increase (5%) was equivalent to the ~5% increase in Hb mass or RCV previously reported in several natural‐altitude LHTL studies . According to a power analysis of previous results showing an increase in VO 2 max from 63.8 ± 1.4 to 66.3 ± 1.8 mL/min/kg after LHTL intervention (means ± SD), a sample size of 8 subjects provides a 95% power to detect a 3.9% change in VO 2 max with a two‐sided α of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…The ECOs method has been recently used in a dozen of peer-reviewed papers with elite and high level athletes (Debevec et al, 2015; Hauser et al, 2016; Saugy et al, 2016; Villaño et al, 2016). Further studies should focus on training tolerance between different athletes' disciplines but including biomarkers to relate these theoretical training load comparisons and discriminate between hormonal status, muscle damage, oxidative stress levels or others.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some physiological responses such as the erythropoietic (Hauser et al . ) and the cerebral oxygenation/perfusion (DiPasquale et al . ) do seem unaffected by the differential P B .…”
Section: Maximal Changes In Barometric Pressure (Pb) and ‘Calculated’mentioning
confidence: 99%